Peran Pasar Tradisional Dalam Meningkatkan Minat Perempuan Dalam Berdagang (Studi Pada Komunitas Mama-Mama Etnis Timor di Pasar Tradisional Penfui-Kupang) - Emiliana Martuti Lawalu; Adrianus Ketmoen (Jurnal Inada: Kajian Perempuan Indonesia di Daerah Tertinggal, Terdepan, dan Terluar, 2022)
The market is a picture of humans who have needs. Markets also often involve humans entering into agreements voluntarily. The aim of this study is to examine traditional marketplace’s roles in order to increase the interest of ethnic Timorese women in trading. The interest in trading of ethnic Timorese women is observed through their presence on every market day – Monday and Friday, from 06.00 WITA to 11.00 WITA. They come from the surrounding villages to sell. The types of goods it sells include: Vegetables, Tomatoes, Chilies, Bananas, Corn, Rice, Chicken Eggs, Kampung Chicken, Sweet Potato Leaves, Papaya Leaves and Flowers, Coconut and Coconut Oil, Young Coconuts. The goods sold are placed on sacks that are spread on the ground. They sit guard while interacting with buyers. However, this selling model has resulted in the market being less organized and less organized, and also causing road congestion.